2000
DOI: 10.1243/0957650001538173
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for control of splitting ratios of particulate materials at bifurcations in pneumatic conveying pipelines

Abstract: In this paper the negative effect on the efficiency of coal-fired power generating stations, caused by unequal split ratios of pulverized fuel in pipeline branches downstream from bifurcations, is identified. Five active techniques for controlling split ratios have been developed and tested on a test-scale rig. Three of the five techniques were deemed to have potential for retrofitting into existing power generating stations and have been tested in detail on a large pilot-scale rig. The observations and the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The system was inherently unstable and experienced serious problems. Similar phenomena have occurred in PF‐fired boilers where a significant contributor to the inefficiency of PF‐fired boilers can be unequal fuel distribution to the burners 8. The pneumatic conveying pipeline that carries the PF from a mill to the furnace typically bifurcates two or three times to feed four or eight burners.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The system was inherently unstable and experienced serious problems. Similar phenomena have occurred in PF‐fired boilers where a significant contributor to the inefficiency of PF‐fired boilers can be unequal fuel distribution to the burners 8. The pneumatic conveying pipeline that carries the PF from a mill to the furnace typically bifurcates two or three times to feed four or eight burners.…”
Section: Introductionmentioning
confidence: 69%
“…Maldistribution can negatively affect industrial equipment, e.g., by causing decreased cyclone capture efficiency,3, 8 differential erosion, differential fouling and more frequent shutdowns. For example, early fluidized bed reactors for the production of ethylene oxide and hydrocarbon synthesis featured multiple open vertical heat transfer tubes of equal length and diameter through which the fluidized suspension was intended to pass uniformly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a major problem related to distribution of pulverized fuel through large parallel coalfired boilers. [14][15]22 Also numerical studies by Schneider et al 13 showed that upstream nonuniformities can play a significant role in flow distribution through parallel pipes. In another study, Yue et al 12 reported maldistribution of gas-solids flow through identical multicyclones at the top exit of a CFB boiler.…”
Section: Introductionmentioning
confidence: 99%